Protein profiling as early detection biomarkers for TiO2 nanoparticle toxicity in Daphnia magna - Sá-Pereira, Paula (Ecotoxicology (London, England), 2018)
The mode of action for nanoparticle (NP) toxicity in aquatic organisms is not yet fully understood. In this work, a strategy other than toxicity testing was applied to Daphnia magna exposed to TiO2-NPs: the use of nuclear microscopy and the assessment of protein profile. D. magna is a keystone species broadly used as a model system in ecotoxicology. Titanium (Ti) was found in the D. magna digestive tract, mainly in the gut. The penetration of Ti into the epithelial region was greater at higher exposure levels and also observed in eggs in the brood pouch. The protein profile of individuals exposed to different concentrations showed that 2.8 and 5.6 mg/L TiO2-NP concentrations induced an over-expression of the majority of proteins, in particular proteins with molecular weight of ∼120, 85 and 15 kDa, while 11.2 mg/L TiO2-NP had an inhibitory effect on protein expression. The Matrix-assisted laser desorption ionization with tandem time of flight mass spectrometry (MALDI-TOF/TOF MS) analysis of these proteins consistently identified them as vitellogenin (Vtg)-like proteins, associated with enzymes involved in redox balance. These results indicate that Vtg-like proteins are up-regulated in D. magna exposed to TiO2-NPs. Vitellogenesis is associated with the reproduction system, suggesting that TiO2-NP exposure can impair reproduction by affecting this process. The precise mode of action of TiO2-NPs is still unclear and the results from this study are a first attempt to identify specific proteins as potential markers of TiO2-NP toxicity in D. magna, providing useful information for future research